Social determinants of awareness and behavior regarding STDs and HIV/AIDS among ever married women in Bangladesh - Rana, Juwel (Family Medicine & Primary Care Review, 2016)
Background . About 8,900 people are living with HIV/AIDS, and 1,000 AIDS-related deaths had been reported in Bangladesh by the end of 2014. Objectives . The study investigates the social determinants of awareness and behavior regarding STDs and HIV/AIDS among ever married women in Bangladesh. Material and methods. This cross-sectional research extracted data concerning 17,828 ever married women from the Bangladesh Demographic and Health Survey (BDHS) in 2014. The chi-square (χ2) and multinomial logistic regression model were used to identify the factors associated with knowledge, awareness and behavior concerning STDs and HIV/AIDS. Results . Overall, 28.6% of examined ever married women have never heard of STDs or HIV/AIDS nor any of their prevention methods. Also, only 15.6% of reported women were the decision makers regarding the use of contraception during sexual intercourse, and 91.3% of women had the capacity to refuse sexual contact with their STD-infected husband/partner. Women who belong to households classified as lower class (OR = 0.525, 95% CI = 0.461–0.598) or middle class (OR = 0.643, 95% CI = 0.564–0.733) had less comprehensive knowledge and awareness of STDs and HIV/AIDS than those categorized as upper class. Women at a level of education below secondary (OR = 0.200, 95% CI = 0.179–0.223) also had less comprehensive knowledge and awareness than highly educated women. Moreover, women living in an urban residence (OR = 1.141, 95% CI = 1.003–1.297) were more likely to make the decision of using contraception and (OR = 1.546, 95% CI = 1.351–1.770) more likely to refuse sexual contact with an STD-infected husband/partner than their rural counterparts. Formally unemployed women (OR = 0.894, 95% CI = 0.793–1.010) were less likely to refuse sexual intercourse with an STD-infected husband than employed women. Conclusions . Social determinants such as education, wealth and media exposure determine the level of knowledge and awareness and affect the behavior of women concerning STDs and HIV/AIDS.